PENGARUH ENTERPRISE RISK MANAGEMENT DISCLOSURE, UKURAN PERUSAHAAN DAN LEVERAGE PADA NILAI PERUSAHAAN SEKTOR PERBANKAN - Shofian Jaswadi, Errik; Sri Harta Mimba, Ni Putu; Suartana, I Wayan; Nyoman Budiasih, Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024, 2024)
The purpose of this study is to find out the effect of enterprise risk management disclosures on company value, the effect of company size on company value and the influence of leverage on company value. The location and subject of data collection in this research is carried out by companies in the banking sector listed on the Indonesian Stock Exchange (IDX) for the 2016-2020 period which are available at www.x.id available at www.x.id. The research sample is public banks listed on the IDX for the 2016-2020 period as many as 13 banks. The data collection technique uses financial statement documentation. Analysis of data using regression test, determination test, F test and t test. Based on the results of the analysis, it can be seen that the disclosure of enterprise risk management has a significant and positive impact on the value of the company. Likewise with the size of the company. Firm size variable also has a significant and direct role in increasing firm value. However, unlike leveregae, this variable has a negative impact on firm value. Increasing the leverage ratio can reduce the value of the company.